2000
DOI: 10.1046/j.1365-3083.2000.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Electroelution of Polyacrylamide Gels for the Purification of Single Proteins from Mycobacterium tuberculosis Culture Filtrate

Abstract: Culture filtrate from Mycobacterium tuberculosis contains protective molecules which have been used successfully in experimental vaccines against tuberculosis. Despite an increasing number of mycobacterial proteins being characterised, a major effort is still needed to get an overview of the many potentially interesting molecules in culture filtrate. In this study we describe a high throughput method for purification and biological evaluation of protein components in complex protein mixtures. The method presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
6
1
5
Order By: Relevance
“…Moreover, recombinant M. tuberculosis GS was abundantly exported by M. smegmatis while very little of the endogenous M. smegmatis GS was released (30). Others have also identified M. tuberculosis GS in culture filtrates (55,56,62,69). In this study, we found a somewhat lower percentage of total GS (8 to 14%) in M. tuberculosis culture filtrates compared with our previous work (33%) and that of Raynaud et al (17%) (55).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Moreover, recombinant M. tuberculosis GS was abundantly exported by M. smegmatis while very little of the endogenous M. smegmatis GS was released (30). Others have also identified M. tuberculosis GS in culture filtrates (55,56,62,69). In this study, we found a somewhat lower percentage of total GS (8 to 14%) in M. tuberculosis culture filtrates compared with our previous work (33%) and that of Raynaud et al (17%) (55).…”
Section: Discussioncontrasting
confidence: 56%
“…In contrast, although there was a readily detectable quantity of MDH in the culture filtrate at all time points (10 to 70 mU per ml of original culture VOL. 69,2001 EXPORT OF GS AND SOD BY MYCOBACTERIA 6355 volume), this extracellular MDH activity represented less than 0.5% of the total MDH activity. The SDS-PAGE results were consistent, showing no accumulation of MDH in the culture filtrate.…”
Section: Resultsmentioning
confidence: 92%
“…Although their functions have not been established, these proteins have been considered as antigens, able to distinguish between tuberculosis clinical states, or attractive targets for the development of new drugs, vaccines and diagnostic strategies for TB [58-60]. …”
Section: Discussionmentioning
confidence: 99%
“…The second fractionation by gel filtration was unsatisfied for narrow separation (data not shown). Weldingh et al [32,33] and Bhasker et al [34] used a preparative two‐dimensional gel for fractionation, while another study [29] used a combination of classical chromatographic methods and a multi‐elution method using PAGE gels to search for reliable antigens. Similarly, we used a combination of DEAE ion‐exchange chromatography and narrow molecular mass fractionation from SDS–PAGE gels, which proved more effective for identifying valuable proteins from the complex antigen system.…”
Section: Discussionmentioning
confidence: 99%